Non-traumatic intestinal perforation in the regional hospital Borgou of Benin: epidemiological and therapeutic characteristics - ALLODE, S Alexandre; DOSSOU, FRANCIS MOÏSE DJIDÉNOU; HODONOU, M Adrien; SETO, D M; GBESSI, GASPARD DANSOU; TAMOU SAMBO, BIO; OLORY TOGBE, JEAN LEON (My University, 2017)
Background: Non-traumatic small bowel perforation is common condition in our income countries. This study aims to determine the pattern of non-traumatic intestinal perforation in our environment. Methods: The demographics, clinical features, relevant investigations, surgery performed and outcome of all the patients confirmed at surgery with intestinal perforation were collected for five years and the data analyzed using version 3.5.1 of Epi Info. Results: Out of the 69 cases involved in this study, there were 46 (66.7%) males and 23 (33.3%) females with a male/female ratio of 2; their mean age was 22.5±13.7 years (range 2 - 68 years). Young people in school constituted 23 (33,34%) of the cases and typhoid intestinal perforation was responsible for 64 (92.8%) cases while ischemic perforation as a result of postoperative flange, strangulated hernia and acute intussusception was responsible in 5 (7.2%) cases. The average duration before presentation in the hospital was 3 days while the average duration between presentation at the hospital and surgery was 2 days. The surgery offered was simple closure after freshening the edges in 35 (50.7%) cases, resection and anastomosis in 28 (40.5%) cases and resection with ileostomy in 6 (8.8 %) cases. The immediate postoperative course was uneventful in 64 (92.8%) case while the mortality was 10 (14.5%). The cause of death was not identified in 3 cases. The average hospital stay was 14.5±12.8 days with extremes of 7 and 55 days. Conclusions: NTIP is relatively common among the causes of widespread acute peritonitis in sub-Saharan Africa and its management remains difficult with high mortality.
Keywords: Acute peritonitis; Non-traumatic perforation; Prognosis; Treatment